Diabetes Mellitus Tipe II Faktor Resiko, Diagnosa, dan Tatalaksanaan - Lira, Anggraini syafri; Marni, Linda; Asmaria, Mike; Yessi, Hilma (Jurnal Keperawatan Medika, 2025)
Type II Diabetes Mellitus is a chronic disease characterized by elevated blood glucose levels due to impaired insulin production or utilization. According to the World Health Organization (WHO), in 2024, the number of people with diabetes reached 830 million globally. At Aisyiyah Hospital in Pariaman, Type II Diabetes Mellitus ranks third among the ten most common diseases.This study aims to provide nursing care to patients with Type II Diabetes Mellitus in the Mina Ward of Aisyiyah Hospital, Pariaman. The subject of this case study is Mr. I, who was hospitalized from February 25 to March 1. The methods used in this study included direct observation, physical examination, interviews, and documentation review.The identified nursing problems included: Unstable,blood glucose levels Acute pain, Impaired skin integrity,Anxiety,Risk of nutritional deficit, Risk of infection, Disturbed sleep pattern,The evaluation results showed that some problems remained unresolved, including: Unstable,blood glucose levels,Impaired skin integrity,Risk of infection, Recommendations were given to the patient and family, with the expectation that they can provide home care, anticipate complications, and offer continuous family support. This is intended to help the patient maintain a proper diet and healthy lifestyle, thereby preventing an increase in blood glucose levels.